Aspects of the Roughing Process by Milling with the Milling Heads with Removable Plates on NC Lathe of the Worms. (2015) - Albu, Sorin Cristian; Bolos, Vasile
Abstract: In this paper there are presented aspects regarding roughing process of cylindrical worms with large module on NC turning and milling center. Conventionally, worm of worm gears have been made on dedicated machines using dedicated tools. These machines are for mass production of worm gear. Small companies cannot invest in these machines especially if their core product is something other than gear manufacture. For the manufacture of worms are not required special tools, all that is required in the roughing process on the NC Lathes are standard tools such as milling heads with removable plates or mono-block frontal-cylindrical milling tools. From economic reasons we insist on roughing research using milling heads with removable plates. The study highlights the fact that it can use in the roughing process of the worms on NC lathe the milling tools with removable plates the cost in this case is less than if we use in roughing process milling tools from mono-block carbide. Important is the Mills positioning in relation to the middle goal of the worm. Determination of the position of the milling head is done based on a computation already submitted in a previous work, determining the parameters of milling is done taking into account the manufacturer's recommendations and testing tools. The tool path has been chosen so that milling to make in advance and counter advance sense, so that we can obtain the tool path for the best sustainability tool.